Maximum sustainable yield from interacting fish stocks in an uncertain world: two policy choices and underlying trade-offs. (28th July 2016) - Farcas, Adrian; Rossberg, Axel G.
Abstract : The case of fisheries management illustrates how the inherent structural instability of ecosystems can have deep-running policy implications. We contrast 10 types of management plans to achieve maximum sustainable yield (MSY) from multiple stocks and compare their effectiveness based on a management strategy evaluation (MSE) that uses complex food webs in its operating model. Plans targeting specific stock sizes (B MSY ) consistently led to higher yields than plans targeting specific fishing pressures (F MSY ). A new self-optimizing control rule, introduced here for its robustness to structural instability, led to intermediate yields. Most plans outperformed single-species management plans with pressure targets that were set without considering multispecies interactions. However, more refined plans to "maximize the yield from each stock separately", in the sense of a Nash equilibrium, produced total yields comparable to plans aiming to maximize total harvested biomass, and were more robust to structural instability. Our analyses highlight trade-offs between yields, amenability to negotiations, pressures on biodiversity and continuity with current approaches in the European context. Based on these results, we recommend directions for developments of EU fisheries policy.